Impacts of Graded Doses of Zincsulfate on Caspase-3 Enzyme Level and Myocardial Apoptosis in Mitoxantrone-induced Cardiotoxicity in Rats - Taif M. Maryoosh (Journal of Global Pharma Technology, 2019)
Zinc is regarded as a necessary mineral for cell division and the production of DNA and protein; furthermore, such mineral has a main role in alleviating cardiovascular diseases and may have protective effect in coronary artery disease. Mitoxantrone is an anthracenedione antineoplastic agent used in the treatment of leukemia, lymphoma, breast and prostate cancer; moreover, such drug can induce cardio toxicity in up to 18% of treated patients which is mainly characterized by the development of left ventricular dysfunction, which is manifested as decreased left ventricular ejection fraction and congestive heart failure. Objective: This study is designed to investigate the impacts of graded doses of zinc sulphate on mitoxantrone-induced cardio toxicity in rats via exploring the role of apoptosis in this toxic effect. Methods: Forty-eight adult rats of both sexes were utilized in this study; the animals were randomly divided into six groups of 8 animals each. Group I: distilled water (negative control). Group II: orally-administered zinc sulfate (15mg/kg/day) Group III: orally-administered zinc sulfate (30mg/kg/day).Group IV: Intraperitoneally injected with a mitoxantrone at a dose (2.5 mg/kg) to reach a total cumulative dose of 7.5 mg/kg on day 20. Group V: Orally-administered zinc sulfate at a dose (15mg/kg/day) with an intraperitoneal injection of mitoxantrone at a dose (2.5 mg/kg) was administered to reach the total cumulative dose of 7.5 mg/kg on day 20.Group VI: Orally-administered zinc sulfate at a dose (30 mg/kg/day) with an intraperitoneal injection of mitoxantrone at a dose (2.5 mg/kg) to reach total the cumulative dose of 7.5 mg/kg on day 20. Forty-eight hrs after the end of treatment duration (i.e. at day 22nd), each animal was euthanized by diethyl ether and ketamine, and then after cervical dislocation, the heart of each animal was excised for homogenate preparation to estimate the activity level of caspase-3 enzyme and to detect DNA fragmentation by the utilization of terminaldeoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick-end labeling (TUNEL) assay. Results: Oral administration of zinc sulfate [(15mg/kg/day with total cumulative dose (7.5 mg/kg) of mitoxantrone] (Group V) resulted in non-significant (P>0.05) difference in caspase-3 level in the cardiac tissue homogenate compared to the corresponding  levels in group of rats intraperitoneally injected with total cumulative dose of 7.5 mg/kg of mitoxantrone (Group IV). In contrast, there were significant reduction (P<0.05) incaspase-3 level in the cardiac tissue homogenate of rats orally-administered zinc sulfate [(30 mg/kg/day) with total cumulative dose (7.5mg/kg) of mitoxantrone] (Group VI) compared to the corresponding levels in group of rats intraperitoneally-injected with total cumulative dose of 7.5mg/kg of mitoxantrone (Group IV). In addition, there was an improvement in the immunohistochemistry of rats’ heart in Group VI; where, numbers of the apoptotic cells were reduced compared to Group IV. Conclusion: Zinc sulfate at a dose (30 mg/kg/day) inhibits mitoxantrone-triggered cardiomyocyte apoptosis.Keywords: Mitoxantrone, Cardiotoxicity, Zinc sulfate, TUNEL-assay, Caspase-3.